2001
DOI: 10.7863/jum.2001.20.9.973
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of time allocation and reimbursement for routine obstetric ultrasonography.

Abstract: Resource use within the ultrasonography department may be improved by reassigning clerical and custodial duties from sonographers to other personnel. Although differential reimbursement exists, no statistically significant difference in resource use between initial and repeated examinations was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Stewart et al 1 found that 37% of sonographer time is spent performing nonimaging data entry and custodial tasks. With salaries for sonographers on the rise, it has always made sense to me that less expensive medical assistants be employed by midsize to large ultrasound imaging departments to assist in duties such as facilitating patient flow, data entry, restocking supplies, and room preparation and cleanup.…”
Section: Nonimaging Responsibilitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Stewart et al 1 found that 37% of sonographer time is spent performing nonimaging data entry and custodial tasks. With salaries for sonographers on the rise, it has always made sense to me that less expensive medical assistants be employed by midsize to large ultrasound imaging departments to assist in duties such as facilitating patient flow, data entry, restocking supplies, and room preparation and cleanup.…”
Section: Nonimaging Responsibilitiesmentioning
confidence: 99%
“…Stewart et al 1 failed to evaluate or discuss the nonimaging, but professional, duties performed by the sonographer. The sonographer's responsibilities have grown over the years.…”
Section: Nonimaging Responsibilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…16 The viability of the volume measurement of Endres and Cohen is questionable because, "Each volume was obtained in approximately 10 minutes." At a time when insurance and health maintenance organization corporations, as well as others, are urging sonographers to do more examinations, with fewer measurements, in less and less time, [22][23][24][25] it is doubtful that more time-consuming methods will gain widespread acceptance in the current economic atmosphere. This is a subject that is important to sonography and clearly needs more research now that true 3D imaging is available to us.…”
Section: Three-dimensional Fetal Brain Volumesmentioning
confidence: 99%